Ovarian cancer pathology characteristics as predictors of variant pathogenicity in BRCA1 and BRCA2 - O'Mahony, Denise G; Ramus, Susan J; Southey, Melissa C; Meagher, Nicola S; Hadjisavvas, Andreas; John, Esther M; Hamann, Ute; Imyanitov, Evgeny N; Andrulis, Irene L; Sharma, Priyanka; Daly, Mary B; Hake, Christopher R; et al. (British journal of cancer, 2023)
BACKGROUND: The distribution of ovarian tumour characteristics differs between germline BRCA1 and BRCA2 pathogenic variant carriers and non-carriers. In this study, we assessed the utility of ovarian tumour characteristics as predictors of BRCA1 and BRCA2 variant pathogenicity, for application using the American College of Medical Genetics and the Association for Molecular Pathology (ACMG/AMP) variant classification system. METHODS: Data for 10,373 ovarian cancer cases, including carriers and non-carriers of BRCA1 or BRCA2 pathogenic variants, were collected from unpublished international cohorts and consortia and published studies. Likelihood ratios (LR) were calculated for the association of ovarian cancer histology and other characteristics, with BRCA1 and BRCA2 variant pathogenicity. Estimates were aligned to ACMG/AMP code strengths (supporting, moderate, strong). RESULTS: No histological subtype provided informative ACMG/AMP evidence in favour of BRCA1 and BRCA2 variant pathogenicity. Evidence against variant pathogenicity was estimated for the mucinous and clear cell histologies (supporting) and borderline cases (moderate). Refined associations are provided according to tumour grade, invasion and age at diagnosis. CONCLUSIONS: We provide detailed estimates for predicting BRCA1 and BRCA2 variant pathogenicity based on ovarian tumour characteristics. This evidence can be combined with other variant information under the ACMG/AMP classification system, to improve classification and carrier clinical management.
Keywords: nádory prsu; BRCA1 Protein; Female; nádory vaječníků; Virulence; BRCA2 Protein; protein BRCA2; genetická predispozice k nemoci; Humans; ženské pohlaví; Ovarian Neoplasms; Breast Neoplasms; lidé; virulence; Genetic Predisposition to Disease; protein BRCA1